2018
DOI: 10.3758/s13428-018-1055-2
|View full text |Cite
|
Sign up to set email alerts
|

RMSEA, CFI, and TLI in structural equation modeling with ordered categorical data: The story they tell depends on the estimation methods

Abstract: In structural equation modeling, application of the root mean square error of approximation (RMSEA), comparative fit index (CFI), and Tucker-Lewis index (TLI) highly relies on the conventional cutoff values developed under normal-theory maximum likelihood (ML) with continuous data. For ordered categorical data, unweighted least squares (ULS) and diagonally weighted least squares (DWLS) based on polychoric correlation matrices have been recommended in previous studies. Although no clear suggestions exist regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
608
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 919 publications
(642 citation statements)
references
References 40 publications
10
608
0
24
Order By: Relevance
“…When tested in a post-hoc model covarying the two items, a non-significant Chi-square (p > 0.05) and better fit indices with RMSEA < 0.05 were obtained. Xia and Yang state that further studies are needed to seek alternative methods for goodness-of-fit evaluation with ordered categorical data [35]. Shi et al has demonstrated that SRMR is relatively free from the choice of estimation method and the same population cut-offs can be applied regardless of the estimation method employed [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When tested in a post-hoc model covarying the two items, a non-significant Chi-square (p > 0.05) and better fit indices with RMSEA < 0.05 were obtained. Xia and Yang state that further studies are needed to seek alternative methods for goodness-of-fit evaluation with ordered categorical data [35]. Shi et al has demonstrated that SRMR is relatively free from the choice of estimation method and the same population cut-offs can be applied regardless of the estimation method employed [34].…”
Section: Discussionmentioning
confidence: 99%
“…Four other approximate fit indices were considered: RMSEA < 0.050 and < 0.080 for close and reasonable fit, respectively: Comparative fit index (CFI) and Tucker-Lewis Index (TLI) of > 0.900 and > 0.950 were considered for acceptable and excellent fit, respectively [32]; Standard Root Mean Square Residual (SRMR) of < 0.05 was also considered because this index is independent of the estimator used [33]. Since we used the DWLS estimator for our analysis, SRMR has been recommended as the main index to test model fit [34][35][36][37].…”
Section: Construct Validitymentioning
confidence: 99%
“…The 4 specific criteria are (1) CFI>0.9; (2) RMSEA<0.09; (3) SRMR<0.09; (4) chi-square/df <5. [31][32][33] The internal consistency was fair (Cronbach's alpha=0.78). For the PBCS, we assigned 5 items into the factor of routine protective behaviors (RPB), 6 items into post-exposure protective behaviors (PPB), and 3 items into post-exposure risky behaviors (PRB).…”
Section: Confirmatory Factor Analysis (Cfa) For Covid-19 Induced Anximentioning
confidence: 99%
“…They are the degrees of freedom (CMIN/df), comparative fit index (CFI), goodness of fit index (GFI), the Tucker-Lewis index (TLI) and root mean square error of approximation (RMSEA) (Kumar, 2019). CFI, GFI and TLI are indices that measure the incremental fit of the model compared to the fit of the hypothesized model to the fit of the baseline model (a base-line model is a model with the worst fit (Xia & Yang, 2019). TLI is a non-normed index (NNFI) as it is also sometimes referred to (Kumar, 2019).…”
Section: Resultsmentioning
confidence: 99%